2016
DOI: 10.1186/s13019-016-0455-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from cardiac surgery in Jehovah’s witness patients: experience over twenty-one years

Abstract: BackgroundCardiac surgery in Jehovah’s Witnesses may be challenging during the operation and postoperative period given their refusal of blood products. The aim of this study was to document our center’s experience with Jehovah’s Witnesses undergoing major cardiac surgery and to compare surgical outcomes with a matched control group.MethodsWe retrospectively reviewed the demographic, perioperative, and in-hospital postoperative data for 31 Jehovah’s Witness patients undergoing surgery from 1991 to 2012 and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(78 citation statements)
references
References 20 publications
2
76
0
Order By: Relevance
“…The clinical experience in treating cardiac surgery patients who refuse blood products, namely, Jehovah's Witnesses, is perhaps one of the strongest indicators that a restrictive transfusion strategy can be implemented safely. Studies have shown that outcomes among patients who refuse blood products can be similar to low‐risk patients who accept blood products when appropriate perioperative measures are taken . Some centers treating Jehovah's Witness patients have focused exclusively on intraoperative blood saving techniques such as Cell Saver and meticulous closure techniques, while others also include measures such as the use of erythropoietin and iron supplements to treat preoperative anemia and limiting blood collection for routine laboratories .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical experience in treating cardiac surgery patients who refuse blood products, namely, Jehovah's Witnesses, is perhaps one of the strongest indicators that a restrictive transfusion strategy can be implemented safely. Studies have shown that outcomes among patients who refuse blood products can be similar to low‐risk patients who accept blood products when appropriate perioperative measures are taken . Some centers treating Jehovah's Witness patients have focused exclusively on intraoperative blood saving techniques such as Cell Saver and meticulous closure techniques, while others also include measures such as the use of erythropoietin and iron supplements to treat preoperative anemia and limiting blood collection for routine laboratories .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that outcomes among patients who refuse blood products can be similar to low‐risk patients who accept blood products when appropriate perioperative measures are taken . Some centers treating Jehovah's Witness patients have focused exclusively on intraoperative blood saving techniques such as Cell Saver and meticulous closure techniques, while others also include measures such as the use of erythropoietin and iron supplements to treat preoperative anemia and limiting blood collection for routine laboratories . These studies are particularly useful indicators of the ability to safely limit transfusions after cardiac surgery as the Jehovah's Witnesses' strict refusal of any and all blood products prevents the crossover seen in some prospective, randomized trials.…”
Section: Discussionmentioning
confidence: 99%
“…Previous retrospective studies demonstrated that cardiac surgery might be performed in JW with acceptable outcomes [ 2 - 10 ] . Furthermore, retrospective studies that compared mortality and morbidity rates in JW and controls showed leveled results between both groups [ 7 - 10 ] . Bhaskar et al.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the data of case series [ 2 - 6 ] and some controlled studies [ 7 - 10 ] showed that the perioperative and postoperative prognosis of JW is similar to those of patients who do not have restrictions to blood products transfusions. However, the rates of mortality and postoperative complications in patients that undergo cardiac surgery are variable.…”
Section: Introductionmentioning
confidence: 99%
“…The use of four-factor prothrombin complex concentrate (4PCC) to decrease bleeding related to coagulopathy is an alternative to alloBT and is generally acceptable among JW patients. 2 At present, several studies have evaluated the outcomes of patients who refuse blood products based on religious beliefs, [3][4][5][6][7][8][9][10][11][12] but little evidence has assessed the use of 4PCC in this population who undergo cardiac surgery. To our knowledge, this is the first retrospective cohort study evaluating postoperative clinical outcomes of JWs who underwent cardiac surgery that received 4PCC vs those who did not.…”
mentioning
confidence: 99%